2008
DOI: 10.1128/jb.01522-07
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for Different Substrate Specificities of Two ADP-Ribose Pyrophosphatases from Thermus thermophilus HB8

Abstract: ADP-ribose (ADPR) is one of the main substrates of Nudix proteins. Among the eight Nudix proteins ofThermus thermophilus HB8, we previously determined the crystal structure of Ndx4, an ADPR pyrophosphatase (ADPRase). In this study we show that Ndx2 of T. thermophilus also preferentially hydrolyzes ADPR and flavin adenine dinucleotide and have determined its crystal structure. We have determined the structures of Ndx2 alone and in complex with Mg 2؉ , with Mg 2؉ and AMP, and with Mg 2؉ and a nonhydrolyzable ADP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 38 publications
0
28
0
Order By: Relevance
“…14,15,17,18 It has been shown that for EcADPRase, loop L9 undergoes significant conformational changes during catalysis and Glu162 on loop L9 acts as the general base to deprotonate a water molecule that further functions as the attacking nucleophile. 14 As the structural comparison of the hNUDT5-AMPCPR-Mg 2 + complex and the EcADPRase-AMPCPR-Mg 2 + complex shows that Asp164 of hNUTD5 occupies a similar position as that of Glu162 of EcADPRase, Asp164 was thought to be the equivalent residue to function as a general base.…”
Section: Comparison Of the Catalytic Mechanisms Of Adpr Hydrolysis Bymentioning
confidence: 99%
See 2 more Smart Citations
“…14,15,17,18 It has been shown that for EcADPRase, loop L9 undergoes significant conformational changes during catalysis and Glu162 on loop L9 acts as the general base to deprotonate a water molecule that further functions as the attacking nucleophile. 14 As the structural comparison of the hNUDT5-AMPCPR-Mg 2 + complex and the EcADPRase-AMPCPR-Mg 2 + complex shows that Asp164 of hNUTD5 occupies a similar position as that of Glu162 of EcADPRase, Asp164 was thought to be the equivalent residue to function as a general base.…”
Section: Comparison Of the Catalytic Mechanisms Of Adpr Hydrolysis Bymentioning
confidence: 99%
“…13,15 However, a different catalytic mechanism was proposed for Thermus thermophilus ADPRase (TtADPRase) Ndx4 because only two metal ions are found to bind at the active site and thus are suggested to be involved in activation of a conserved water molecule that acts as the nucleophile to attack the α-phosphate of the substrate, and mutation of Glu127, which is considered to be equivalent to Glu162 of EcADPRase, has no effect on the enzymatic activity. [16][17][18] Intriguingly, in the structure of another TtADPRase Ndx2, there are three metal ions bound at the active site and mutation of Glu136 (corresponding to Glu162 of EcADPRase) does decrease k cat by about 12-fold. 18 For eukaryotes, crystal structures of two human ADPRases (hNUDT9 and hNUDT5) have been reported.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Assay for cAMP and cGMP Phosphodiesterases-To determine the phosphodiesterase steady-state kinetic parameters, the following reaction mixture (80 l) was applied to a CAPCELL PAK C18 column as previously described (42). The reaction mixture (100 l), which contained 50 mM Tris-HCl, 100 mM KCl, 5 mM MnCl 2 , 0.1-2 mM cAMP or cGMP, and 1 M TTHA0118 (pH 7.5), was incubated at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Assay for pAp Phosphatase Activity-To determine the pAp phosphatase steady-state kinetic parameters, hydrolytic activity was analyzed by measuring the production of inorganic orthophosphate using a colorimetric assay (42). The reaction mixture (100 l), which contained 50 mM Tris-HCl, 100 mM KCl, 5 mM MnCl 2 or MgCl 2 , 5-1,000 M pAp, and 0.2 nM TTHA0118 or Mpn140 (pH 7.5), was incubated at 37°C.…”
Section: Methodsmentioning
confidence: 99%